MENGHITUNG EFISIENSI TERMAL PADA ALAT VERTICAL CEMENT MILL PABRIK II PT SEMEN BATURAJA (PERSERO) TBK DAN PENGARUH LAJU ALIR UMPAN SERTA DAYA MOTOR - Heri Arius, Ozy Doresa Omelga; Umbara, Nandika Berito; Safaruddin, Safaruddin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
Vertical Cement Mill is the main tool used in the final process of making cement at PT Semen Baturaja (Persero) Tbk. Vertical Cement Mill is used to mix and grind clinker and corrective materials. In addition, this tool is also used as a dryer by utilizing hot air from the great cooler and grinding roller. The result of this grinding and mixing is called cement. In the Vertical Cement Mill there is also a transport process, namely the transfer of material from the table surface to the next system. The working principle of the clasifier is to block air flow, where when the clasifier rotation speed is high, the lifting power of the product will be low. The mass balance in chemical engineering is centered on chemical reactions, fluid transfer, material shrinkage or enlargement, heat transfer and so on that cause physical and chemical changes. Keywords: PT. Semen Baturaja, Vertical Cement Mill, Neraca Massa, Tujuan.